Recovery of helminth ova from soil in Ibadan metropolis (2012)
The prevalence of soil-transmitted helminth infection was assessed through collection of soil samples from different places in Ibadan South Western Nigeria, using standard parasitological technique. 670 samples were collected from veterinary clinics, residential areas, zoological garden and public places. Two hundred and sixty five were positive for helminth ova. The study revealed an overall prevalence of 39.6%. Veterinary clinics has soil helminth ova prevalence rate of 44.1%, residential areas 60.0% Zoological garden 50.0% and public places 0.0%. Ascarid, Strongyle and Ancylostoma species were identified during the survey